Participation among Children with Arthrogryposis Multiplex Congenita: A Scoping Review. (1st November 2020) - Elfassy, Caroline; Cachecho, Sarah; Snider, Laurie; Dahan-Oliel, Noemi
Abstract: Aim: To explore what is currently known regarding participation among children and youth with arthrogryposis multiplex congenita (AMC) using empirical studies, gray literature, and YouTube videos. The secondary objectives included identifying activity types, outcome measures used, interventions provided, and barriers and facilitators to participation. Method: Empirical studies and gray literature were searched through electronic databases and videos were searched on YouTube. Articles and videos pertaining to participation and youth with AMC were included by two reviewers. Data regarding activity types, location, outcomes measures, interventions, and barriers and facilitators to participation was extracted. Data was critically appraised using specific evaluation criteria. Result: Eleven empirical studies, six gray literature articles and 71 videos met the inclusion criteria. The most common activity types reported in the empirical studies and YouTube videos were active-physical, social, and skill-based activities. Outcome measures included evaluations and questionnaires, none of which were designed to address participation. Interventions did not target participation although the environments could affect participation. Conclusion: The paucity of research indicates a need for future studies of participation in this population. Interventions should target participation and address environmental barriers. Videos provide insight for clinicians, youth, and families to help promote participation in the natural environment.